Hybrid Digital Governance and EdTech Capitalism: The COVID-19 Crisis as a Threat - Enrique-Javie (FahrenHouse, 2021)
This article starts from a theoretical review on the current advance of EdTech capitalism in the definition of the new global educational policies. In it, the aim is to analyze the neoliberal logics that are being introduced in educational systems through the story of an unavoidable future of digital education, promoted again by the large technological corporations, as a result of the confinement and distance education imposed by the global pandemic COVID-19 in much of the world. The new digital governance that is being introduced by BigTech in education is discussed, where public-private hybridization becomes rather public subordination and dependence on the private and if what this hybrid governance is really leading to is a progressive phenomenon of educational uberization. Finally, it is concluded that the solution is not to become an objector to digitization but to «socialize the cloud» and put into the hands of the common the new means of digital production, to advance towards educational digital democracy.